Pengaruh Jenis dan Konsentrasi Bahan Pemlastis terhadap Bioplastik Glukomanan - Nandika A.J, Aditya; Harsojuwono, Bambang Admadi; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 1 (2021): MaretDO - 10.24843/JRMA.2021.v09.i01.p08, 2021)
This research aims to determine the effect of plasticizer types and concentrations on the characteristics of glucomannan bioplastics, and to determine the types and concentrations of plasticizers that can produce glucomannan bioplastics with the best characteristics. This experimental design used a completely randomized design method. Factor I is a type of plasticizer consisting of glycerol, sorbitol, propanol-2, and polyethylene glycol. The second factor is the concentration of plasticizers which consists of 4 levels, namely 0.5%: 1.5%: 2.5%: 3.5%. The experiment resulted in 16 treatment combinations and grouped into 2 groups to obtain 32 experimental units. The data were analyzed for their diversity and continued with the Duncan multiple comparison test. The results showed that the type and concentration of plasticizers had a very significant effect on tensile strength, elongation at break, modulus young, and swelling. The interaction has a very significant effect on tensile strength and expansion and has a significant effect on the elasticity of glucomannan bioplastics. Meanwhile, the type and concentration of plasticizers had no significant effect on the length of biodegradation. The best glucomannan bioplastic was obtained in the treatment of glycerol plasticizers with a concentration of 1.5 % with a tensile strength value of 6.17 MPa, elongation at break of 21.5 0 %, elasticity 28.72 MPa development 25.84 %, and degradation time of 8 days. Bioplastics produced in this study have meet the SNI 7188.7:2016 standards in the elongation test at break and standards ASTM 5336 in the degradation time variables. The resulting bioplastic has not met SNI on the tensile strength, modulus young, and swelling variables. Keywords : bioplastic, glucomannan, glycerol, polyethylene glycol, propanol-2, sorbitol